REGENERATION OF PLANTLETS FROM NODAL CULTURES OF MOMORDICA DIOICA ROXB. - MD. MUSTAFA,; T.N. SWAMY,; S.RAJU,; SK PEER MOHAMMAD,; V. SURESH, (International Journal of Pharma and Bio Sciences, 2012)
The Callus cultures were raised from nodal explants of Momordica dioica Roxb. and the callus was inoculated on MS medium supplemented with different concentrational combinations of 2,4-D, IAA and BAP. Good amount of compact and green callus from nodal cultures was achieved on MS 1 medium fortified with 2.0 mg/l 2,4-D + 1.0mg/l BAP. Regeneration of plantlets were achieved on MS medium fortified with 2.0mg/l BAP + 1.0 mg/l IAA. High frequency of regeneration of plantlets was achieved on the same medium after the sub culture. Later such plantlets were grown for two weeks and rooted on MS +3.0mg/l IBA. The rooted plantlets were grown in green house for hardening and transferred to soil.